ANALYSIS OF FACTORS AFFECTING MEMBERS AND PEOPLE'S TISFACTION FOR SERVICES AGRICULTURE COOPERATIVE IN BAC LIEU PROVINCE - Nguyễn, Tuấn (SCIENTIFIC JOURNAL OF TAN TRAO UNIVERSITY, 2023)
This study was carried out from 06/2022 to 12/2022. Research data was collected from 300 people, including 150 members of agricultural cooperatives and 150 fammers outside the cooperatives, the peoples use the services of argicultural cooperatives in Bac Lieu province. Applying the exploratory factor analysis method model, the people's satisfaction with the services of the cooperative is affected by the following factors: (1). Timely response when users meet with difficulties; (2). Ensuring that people have peace of mind when using the service; (3). Infrequent dispute; (4). Taking interest in the family members and citizens; and (5). Equipment, qualitative machine. In particular, Equipment, qualitative machine is the most affected factor (0.418) to the satisfaction of the people for the services of the current agricultural cooperatives in Bac Lieu province.